Effect of selected catechins on doxorubicin antiproliferative efficacy and hepatotoxicity in vitro - Rudolfová Petra; Hanušová Veronika; Skálová Lenka; Bártíková Hana; Matoušková Petra; Boušová Iva (Acta Pharmaceutica)
Catechins may influence both desirable and undesirable effects of many drugs. In this study, the in vitro effect of (+)-catechin, (-)-epicatechin, (-)-epigallocatechin, (-)-epicatechin gallate, and (-)-epigallocatechin gallate (EGCG) on the efficacy of anticancer drug doxorubicin (DOX) was studied in HCT-8 cancer cells. Rat hepatocytes were used to study the influence of EGCG on DOX hepatotoxicity. Cell proliferation and viability were studied by 3-[4,5-dimethylthiazol- 2-yl]-2,5-diphenyl tetrazolium bromide and neutral red uptake test assays. Formation of reactive oxygen species (ROS) was determined using the dichlorofluorescein assay. All of the studied catechins (1-25 μmol L-1) had no effect on the proliferation of intestinal cancer cells and did not affect the antiproliferative effect of DOX (1-8 μmol L-1) in these cells. Moreover, EGCG at 25 μmol L-1 increased the viability of isolated hepatocytes and significantly protected these cells against DOX-induced toxicity and ROS production. Consumption of EGCG during DOX therapy seems to be safe and beneficial, since EGCG does not decrease DOX anticancer efficacy and could ameliorate DOX hepatotoxicity